A botulinum toxin A treatment algorithm for de novo management of torticollis and laterocollis. Issue 2 (12th September 2011) - Hefter, Harald; Kupsch, Andreas; Müngersdorf, Martina; Paus, Sebastian; Stenner, Andrea; Jost, Wolfgang
Abstract : Objectives: Few studies have investigated the injection patterns for botulinum toxin type A for the treatment of heterogeneous forms of cervical dystonia (CD). This large, prospective, open-label, multicentre study aimed to evaluate the effectiveness and safety of 500 U botulinum toxin A for the initial treatment according to a standardised algorithm of the two most frequent forms of CD, predominantly torticollis and laterocollis. Design: Patients (aged ≥18 years) with CD not previously treated with botulinum neurotoxin therapy were given one treatment with 500 U Dysport, according to a defined intramuscular injection algorithm based on clinical assessment of direction of head deviation, occurrence of shoulder elevation, occurrence of tremor (all evaluated using the Tsui rating scale) and hypertrophy of the sternocleidomastoid muscle. Results: In this study, 516 patients were enrolled, the majority of whom (95.0%) completed treatment. Most patients had torticollis (78.1%). At week 4, mean Tsui scores had significantly decreased by −4.01, −3.76 and −4.09 points in the total, torticollis and laterocollis populations, respectively. Symptom improvement was equally effective between groups. Tsui scores remained significantly below baseline at week 12 in both groups. Treatment was well tolerated; the most frequent adverse events were muscular weakness (13.8%), dysphagia (9.9%) and neck pain (6.6%). Conclusions: Dysport 500 U is effective and well tolerated for the de novo management of a range of heterogeneous forms of CD, when using a standardised regimen that allows tailored dosing based on individual symptom assessment. Clinical trials information: (NCT00447772 ; clinicaltrials.gov )